Behavior of Reinforced Concrete Beams with effect of Stiffened Plates - Al Amli, Ali Sabah; Shakir, Laith; Abdulredha, Ali; Al-Ansari, Nadhir (Civil Engineering Journal, 2019)
This study presents experimental work including an investigation conducted on five simply supported reinforced concrete beams under pure torsion. First beam without strengthening as a control beam. The other four beams were strengthened externally by bolted thin steel plates. For this test the load was applied gradually. The torque was increased gradually up to failure of the beam.Â  The variables were the thickness and height of the steel plate that was externally connected to both sides of the rectangular reinforced concrete beam. The test results for the beams discussed are based on torque-twist behavior. The experimental results show that the attachment of thin steel plates by mechanical means to beams provides a considerable improvement in the torsional behavior of the reinforced concrete beams. Comparable to the reference beam, the maximum increase in the cracking and the ultimate torque of the composite beam was recorded for the reinforced concrete beam that strengthen by steel plate of (150) mm height, (2mm) thickness and (50mm) spacing between shear connectors (B1). The results revealed that the cracking torque, ultimate torque, global stiffness of beam and beam ductility for all composite beams increase with the increase of the plate's thickness, plate's height.